Stylistic Manifestation of Author’s «I» in Lesya Ukrainka’s Literary and Critical Works (Linguostylistic Studies, 2014)
This article deals with the peculiarities of stylistic manifestation of author’s «I» in Lesya Ukrainka’s literary and critical works. Two forms of author’s presence experession explicit and implicit have been analyzed. The dominance of  indirect means have been identified. It has been revealed that among the open forms of stylistic representation of «I» prevail the pronouns of the first person singular and plural. They predetermine the publicist and emotionality of content. Great attention is devoted to the metatextual units which convey the evaluation of the information Metatextual units are the most frequently used  elements which demonstrate the expression of author’s «I». It has been investigated that the choice of expression of author’s «I» is predetermined not only by the genre but also by commonly accepted demands in definite spheres of communication. It provides the effective communicative act between the author and the reader. Key words: communicative act, communicative behavior, author’s «I», metatextual units, explicit and implicit means of expression. References